Pengembangan Modul Matematika Berbasis Pendidikan Rumah Dalam Pembelajaran Jarak Jauh Era Pandemi Covid-19 - Aulia Anggi Prastiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to: (1) develop the mathematics module home-based education in distance learningin the era of the covid-19 pandemic that can be used in learning (2) determine the feasibility of themodule home education-based mathematics in pandemic era distance learning covid-19 based on anassessment by module experts, material experts, students and parents.This research is a type of module media development research which carried out at home usingthe Research and Development model Development (R&D) Borg and Gall which has been modified(Sugiyono, 2013:21) namely: exploring potentials and problems, data collection, product design,validation design, design revision, product trial, product revision, usage test, and revision product. Thesubjects involved in this study consisted of: 2 module media experts, 2 material experts, and 25 studentsand 25 parents of grade IV SD Negeri Gelangan 1 Magelang District, Central City, Magelang City.Method of collecting data done by using the method of observation, interviews, and questionnaires. Testthe validity of the respondent's questionnaire using expert judgment (instrument) in consultation withexperts). Prerequisite test of instrument analysis consists of test validity and reliability test. Dataanalysis using Likert scale.The results of this study indicate that: (1) math-based module home education in distance learningin the era of the covid-19 pandemic for classes IV SD has been developed through nine stages and canbe used in learning. (2) home education-based mathematics module in distance learning in the era ofthe covid-19 pandemic for grade IV SD has been tested eligibility by experts, students and parents.Eligibility results by media experts module obtained a score of 3.8 with very good criteria, the feasibilityof the module by material expert 3.2 with very good criteria, the feasibility of the module by students atthe stage product trial (small scale) by 91% and parents at the product trial stage (small scale) by 88%,and students at the trial stage (large scale) by 96.20% and parents at the product trial stage (largescale) of 96.50%. The results of this study prove that the mathematics module based on home educationin distance learning in the era of the covid-19 pandemic on the eyes Mathematics lessons for grade IVSD are suitable for use in learning.